The Effectiveness of KNOS-KGS Learning Model to Improve Generic Science Skill and Biology Student Learning Outcomes SMA PGRI 1 Banjarmasin - Rezky Nefianthi (Proceeding Biology Education Conference: Biology, Science, Enviromental, and Learning, 2015)
This study aims to determine the effectiveness of the model KNOS-KGS, to improve the learning outcomes of Biology at the ecosystem material in class X SMA PGRI 1 Banjarmasin. This research is a classroom action research, conducted in two cycles. Each cycle is done with two meetings. This study was conducted on 25 students in class X1. The research data is the result of student learning that consists of cognitive learning outcomes such as pretest and posttest. Affective learning outcomes such as student trained in generic skills of science is observed with the observation sheet and any instructional rubric. Data were collected through tests and observation techniques. Results showed that, learning to use a model KNOS-KGS effectively to improve student learning outcomes that have average cognitive achievement ≥ 75, the average generic science skills of 84% in good criteria, and 16% on a very good criteria.Keywords: Generic skills, KNOS-KGS model, learning outcomes